(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the theoretical and methodological foundations and issues of the development of communicative competence of future psychologists. In recent years, a number of activities have been carried out in the country in the field of psychology to train pedagogues and support the activities of practicing psychologists. This article also deals with the development of communicative competence, which is the basis of the basic professional development of future psychologists.